To See the World Through the Eyes of Another - Black, Molly (My University, 2018)
Before studying abroad, the world seemed monstrously unattainable. Traveling was something I had dreamed of doing, but it was so expensive and seemingly far away that I thought the places I had only read about would remain in stories and history. As a lover of people, their pasts, and their cultures, when the opportunity came to pursue a semester abroad, I jumped at the chance. I grew up watching BBC television shows, religiously listening to the Beatles, and being fascinated by the English accent (something I have since come to understand is not a singular, unvarying phenomena). It seemed like a given that England was where I was headed. London itself beckoned for so many reasons, one being that it was the setting of so many stories, shows, and movies I love. Secondly, I simply love big cities. Something about the juxtaposition of old versus new, coupled with the historicity that is so vibrantly present in places where people are constantly moving and making decisions has resulted in me feeling anomalously at home in places like New York, Chicago, San Francisco, etc.